Smart Watering Plant Using Solar - Samion, Norhafiza; Zulkifli, Ezwan; Zainudin, Farid; Mohamad, Maliki (Multidisciplinary Applied Research and Innovation, 2022)
This project intends to solve many problems like reducing wastage of water, harnessing natural energy, and helping humans do work more efficiently. As a result, it have taken the initiative to prevent water waste by developing a smart watering system prototype. It used a solar panel to provide power for the smart irrigation system after the project and the Arduino Uno controller, connect the input (soil moisture sensor) to the output (water pump). The project also created a working prototype of an automated plant watering system and the system operations performed by Arduino Integrated Development Environment (IDE) software. The Arduino Uno is used to operate the Smart Watering Plant Using Solar. When the soil moisture sensor detects that the soil is dry, Arduino will send a signal to the motor to pump water into the soil. It used a solar panel with a 5W power output will provide the power source, the Arduino platform is used for the controller, 3W, 0.18A motor for a water pump and the soil moisture sensor for the irrigation system’s input. As a result, the project is a success, able to provide sufficient water to the plants. Water waste and energy consumption can be reduced. The project uses renewable energy, so it is eco-friendly.